2008
DOI: 10.1359/jbmr.071113
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analyses in a Sample of Individuals With High or Low BMD Shows Association With Multiple Wnt Pathway Genes

Abstract: Using a moderate-sized cohort selected with extreme BMD (n = 344; absolute value BMD, 1.5-4.0), significant association of several members of the Wnt signaling pathway with bone densitometry measures was shown. This confirms that extreme truncate selection is a powerful design for quantitative trait association studies of bone phenotypes.Introduction: Although the high heritability of BMD variation has long been established, few genes have been conclusively shown to affect the variation of BMD in the general p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
99
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(112 citation statements)
references
References 38 publications
11
99
1
1
Order By: Relevance
“…Mutations in WNT3A (c.152A > G, p.K51R) and DKK1 (c.359G > T, p.R120L) have been shown to cause childhood-onset primary osteoporosis, manifested as reduced bone mineral density, peripheral fractures, and/or vertebral compression fractures (Korvala et al 2012). Moreover, common polymorphisms in genes belonging to this pathway have been nominally associated with BMD in Australian postmenopausal women using an extreme phenotype approach (Sims et al 2008). In the current study, we replicated the association of WNT3A and DKK2 polymorphisms with BMD in the Mexican population, providing further evidence of the role of this pathway in BMD variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations in WNT3A (c.152A > G, p.K51R) and DKK1 (c.359G > T, p.R120L) have been shown to cause childhood-onset primary osteoporosis, manifested as reduced bone mineral density, peripheral fractures, and/or vertebral compression fractures (Korvala et al 2012). Moreover, common polymorphisms in genes belonging to this pathway have been nominally associated with BMD in Australian postmenopausal women using an extreme phenotype approach (Sims et al 2008). In the current study, we replicated the association of WNT3A and DKK2 polymorphisms with BMD in the Mexican population, providing further evidence of the role of this pathway in BMD variation.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, LRP5 is recognized as one of the key bone regulatory genes that might influence BMD in the general population, and LRP5 polymorphisms have been consistently associated with BMD in different populations (Richards et al 2008;van Meurs et al 2008;Rivadeneira et al 2009). More recently WNT3A, known to affect osteoblast differentiation (Monroe et al 2012), was found to be associated with BMD in Australian postmenopausal women (Sims et al 2008); a meta-analysis combining five GWAS identified a large linkage disequilibrium (LD) block encompassing LRP4 associated with femoral neck and lumbar spine BMD (Styrkarsdottir et al 2008). It has also been suggested that LRP6 polymorphisms influence BMD (Sims et al 2008;van Meurs et al 2008); however, the results have been conflicting (Mencej-Bedrac et al 2009;Yerges et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study used a design, with extreme truncate selection of unrelated males, aiming to improve power. The approach of studying samples drawn from the extremes of the population distribution of BMD has been used in several linkage studies of BMD variation, 25,27 but rarely in association studies, 28 and to our knowledge, never in samples drawn from the population of males. Owing to our relatively small GWA sample size, no SNP showed evidence of association to either one or both BMD phenotypes at genome-wide significance threshold of 1.7Â10 À7 (0.05/298 783 SNPs).…”
Section: Simulation Studymentioning
confidence: 99%
“…Given that single-nucleotide polymorphisms of SOST that predispose to increased fracture risk and low BMD have been identified recently, (37)(38)(39)(40) the possibility that PTH may be less effective in these populations demands that additional treatment options are made available.…”
mentioning
confidence: 99%